Hubungan Defisiensi Energi Kronis pada Ibu Hamil dengan Kejadian Berat Bayi Lahir Rendah - Siti Mulyani; Wiwin Mintarsih P; Uly Artha Silalahi (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Chronic Energy Deficiency (CED) in pregnant women remains a significant public health problem affecting pregnancy outcomes, particularly Low Birth Weight (LBW). Inadequate maternal energy and protein intake can impair fetal growth and increase the risk of LBW. This study aimed to analyze the association between CED and the incidence of LBW in the working area of Cigeureung Health Center. A quantitative analytical study with a cross-sectional design was conducted involving 170 pregnant women selected through total sampling. Data were obtained from maternal nutritional status records and infant birth weight documentation. Univariate analysis described the distribution of CED and LBW, while bivariate analysis using the Chi-square test assessed the association at a significance level of p < 0.05. The results showed that 15.88% of pregnant women experienced CED and 5.88% of infants were born with LBW. All LBW cases occurred among mothers with CED, with a statistically significant association (p = 0.000). These findings provide context-specific evidence highlighting a complete overlap between maternal CED and LBW, emphasizing the urgent need for early mid-upper arm circumference (MUAC) based screening and targeted nutritional interventions in primary healthcare settings.